A rare case of rectovaginal squamous cell carcinoma in a postmenopausal woman - Celestine He; Daniela Suarez-Rebling; Mona Saleh; Lakshmi Kowtha; Valentin Kolev (Elsevier, 2024)
Primary squamous cell carcinoma of the rectovaginal septum is rare, with only a few previous cases being reported. We present a case of a 55-year-old woman with primary squamous cell carcinoma of the rectovaginal septum, which was discovered after 2 months of postmenopausal bleeding. Her imaging, surgical course, pathology and treatment course are presented here. To our knowledge, this is only the third such reported case in the literature and management underscores the need for multidisciplinary involvement.